Geometric structural design for lead tellurium thermoelectric power generation application. (October 2019) - Wang, Xue; Wang, Hongchao; Su, Wenbin; Mehmood, Fahad; Zhai, Jinze; Wang, Teng; Chen, Tingting; Wang, Chunlei
Abstract: High thermoelectric figure of merits have been achieved in lead telluride (PbTe) alloys recently, which are beneficial for future thermoelectric applications. In this study, a PbTe-based thermoelectric module is constructed by eight pairs of p-type PbTe–8%SrTe and n-type PbTe0.998 I0.002 –3%Sb legs with initial sizes of 3 × 3 × 3 mm 3 . The relationship between multiple geometric parameters and performance of module has been studied by finite-element simulation. The maximum output power ( P max ) of 7.6 W and efficiency ( η max ) of 15.3% have been achieved at ΔT = 500 K for ideal contacted PbTe-based thermoelectric module. Contact resistance must exist in experimental thermoelectric module, so it has been considered in simulation about geometry optimization. The cross-sectional area ratio ( A p /A n ) and height ( H ) show strong dependent relationship to optimize module performance. The larger A p /A n and relatively lower H are propitious to enhance the output power. Moreover, the efficiency is improved at an optimum A p /A n and relatively higher H. In this PbTe-based module, the P max = 4 W is achieved at A p /A n = 1.78 and H = 0.65 mm, while η max = 14% is achieved at A p /A n = 1.64 and H = 13 mm under ΔT = 500 K. The P max and η max are 20% and 65% larger than those of initial design sizes. Thus, geometric structure modification is a good way to improve the performance of thermoelectric applications. Highlights: Cross-sectional ratio ( A p / A n ) and height ( H ) have strongly depended relationship. Larger ratio of A p /A n and relatively lower H easily lead to higher output power. Suitable ratio of A p /A n and relatively higher H can result to higher efficiency. P and η of PbTe-based module are enhanced by 20% and 65% via geometry design.